The Effect Of Training And Work Discipline On The Performance Of Public Works And People's Housing Service Employees In Tebo District - Andriansyah Andriansyah; Dawn Pangestu; Muhammad Asman; Misra Yeni; Asminar Asminar; Delila Fitri Harahab (International Journal of Ecma Science, 2021)
This study aims to determine the effect of training and work discipline on employee performance partially or simultaneously on the performance of employees of the Tebo Regency Public Works and Public Housing Service. The population in this study were 64 people and the sample was 64 respondents. The sampling technique is saturated sampling. The results of the analysis of multiple linear regression equations are: Y = 2.513 + 0.301X1 + 0.640X2 + e. The results of the t-test of the training variable (X1) significant value 0.021 0.05 with a value of tcount ttable (2,371 2,000). The work discipline variable (X2) has a significant value of 0.000 0.05 with tcount ttable (5,308 2,000). The results of the F test are known that the value of Fcount is 51.201 Ftable of 3.15. The value of R Square is 0.627. The coefficient of determination illustrates that the variables of training and work discipline are able to explain the variable of employee performance by 62.7%, while the remaining 37.3% is explained by other variables not included in this research model. Suggestions from this research, increase training for employees and continue to improve employee discipline in order to improve employee performance.